Stevens-Johnson Syndrome in a Child on Phenytoin, Exacerbated with Cefixime - Roka, Yam Bahadur; Shrestha, Sabrina; Roka, Narayani; Karki, Mohan (Journal of Nepal Paediatric Society, 2019)
Steven Johnson syndrome and toxic epidermal necrolysis are rare but potentially life threatening muco-cutaneous disorders. Their incidence ranges from 1.2 to six per million patient-years for Steven Johnson syndrome and 0.4 to 1.2 per million patient-years for toxic epidermal necrolysis. Drugs are the primary cause for these syndromes in majority cases. They might also be due to infections with Mycoplasma Pneumoniae or Herpes Simplex. The mortality ranges from five to 40% in these cases. We report a 10-year old girl who presented with history of multiple skin eruptions involving whole body and oral ulceration for five days. She was a known case of seizure disorder on phenytoin and had been prescribed Cefexime for fever. She was managed with intravenous fluids, corticosteroids, opiates, antacids and topical antibiotics. We want to highlight the possibility of Steven Johnson syndrome following the combination of these two drugs.